Influence of surface heat treatment performed with pulsed Nd: YAG laser on the gain of surface mechanical properties in VP 100 Tool Steel - Crespo, G. S. [UNESP]; Gonçalves, A. C. [UNESP]; Ventrella, V. A. [UNESP] (My University, 2023)
The literature brings several studies about VP 100 steel, tool steel with a bainitic structure used in the mold, and die manufacturing sector, in the face of machining processes. However, few studies deal with the behavior of this steel against the use, directly or indirectly, of welding processes in its manufacture. Thus, this work analyzed the influence on the structure, and on the surface mechanical properties (hardness and wear rate), of the VP 100 steel when submitted to a surface quenching process with laser. Initially, through the use of a Nd:YAG laser system, in the pulsed condition, six different welding conditions were investigated: SG, AR, N, N1, N2, and N3. The six welding conditions were analyzed using Vickers microhardness tests to determine the best conditions for performing the surface tempering treatment. The three conditions (N1, N2, and N3) that presented the best hardness results, both superficially and in the depth range up to 0.30 mm, advanced in the study. The next step consisted of the execution of the surface quenching process, carried out through the execution of successive autogenous weld beads, in the tempering conditions T1, T2, and T3 (analogous to the welding conditions N1, N2, and N3), on the surface of VP 100 steel proof. The heat-treated specimens were analyzed through X-ray diffractograms, and the detection of nitride formation in the post-treatment metal did not occur. Still about the X-ray diffractograms, the data obtained showed a change in the material's structure, from bainitic to martensitic, and a reduction in the size of crystallites in the structures of the three conditions. The wear rate tests showed better results for the harder conditions, with better results being obtained by the T3 condition. Finally, condition T3 was stipulated as the best condition, among those analyzed, for performing surface hardening by laser on VP 100 tool steel, presenting, in addition to an increase in its hardness values, a low wear rate, factors attributed to the formation of a martensitic structure, reduction of crystallite size, and possible nitrogen interstitialization in the metal after heat treatment.
Keywords: Nitrogen; Tempering; Toughness; Wear